The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/cpt.2039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the CYP2C19*17 Allele on Outcomes in Patients Receiving Genotype‐Guided Antiplatelet Therapy After Percutaneous Coronary Intervention

Abstract: Genotyping for CYP2C19 no function alleles to guide antiplatelet therapy after percutaneous coronary intervention (PCI) improves clinical outcomes. Although results for the increased function CYP2C19*17 allele are also reported, its clinical relevance in this setting remains unclear. A collaboration across nine sites examined antiplatelet therapy prescribing and clinical outcomes in 3,342 patients after implementation of CYP2C19‐guided antiplatelet therapy. Risk of major atherothrombotic and bleeding events ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…( b ) Racial/ancestral breakdown of participants included in the clinical trials leading to the approval of the antiplatelets, clopidogrel, prasugrel, and ticagrelor, and pharmacogenomic sub‐analysis conducted within these trials 86,91,115–120 . ( c ) Racial/ancestral breakdown of pharmacogenomic efforts evaluating the association between CYP2C19 and antiplatelet therapy 93,95,121–124 . ( d ) CPIC guidelines for CYP2C19 ‐guided antiplatelet therapy and breakdown of actionable CYP2C19 metabolizer phenotypes by race/ancestry 92 .…”
Section: Clopidogrel: the Aggregate Evidencementioning
confidence: 99%
“…( b ) Racial/ancestral breakdown of participants included in the clinical trials leading to the approval of the antiplatelets, clopidogrel, prasugrel, and ticagrelor, and pharmacogenomic sub‐analysis conducted within these trials 86,91,115–120 . ( c ) Racial/ancestral breakdown of pharmacogenomic efforts evaluating the association between CYP2C19 and antiplatelet therapy 93,95,121–124 . ( d ) CPIC guidelines for CYP2C19 ‐guided antiplatelet therapy and breakdown of actionable CYP2C19 metabolizer phenotypes by race/ancestry 92 .…”
Section: Clopidogrel: the Aggregate Evidencementioning
confidence: 99%
“…However, in in the present analysis as well as previous reports, 8 the H4 metabolite AUC was similar in the UMs and EMs. Furthermore, Lee et al 53 reported that the risk of atherothrombotic events was not significantly different between CYP2C19 UMs and CYP2C19 EMs, indicating that the clinical utility of CYP2C19*17 to guide clopidogrel antiplatelet therapy is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Tiroch et al reported a protective role of CYP2C19 gain of function alleles as carriers of CYP2C19-17 had a lower risk of target-lesion revascularization and MACE when compared to non-carriers ( 21 ). However, Lee et al reported a similar risk of MACE between carriers of CYP2C19-17and non-carrier ( 22 ). In terms of bleeding risk, Sibbing et al reported increased bleeding risk in carriers of CYP2C19-17 ( 23 ), while Lee et al reported similar bleeding risk between carriers and non-carriers ( 22 ).…”
Section: Implications Of Genetic Polymorphismmentioning
confidence: 92%
“…However, Lee et al reported a similar risk of MACE between carriers of CYP2C19-17and non-carrier ( 22 ). In terms of bleeding risk, Sibbing et al reported increased bleeding risk in carriers of CYP2C19-17 ( 23 ), while Lee et al reported similar bleeding risk between carriers and non-carriers ( 22 ).…”
Section: Implications Of Genetic Polymorphismmentioning
confidence: 92%